Javanese Family Ecology - Ismet Sari; Endang Ekowati (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Javanese ethnic in Asahan have a unique way to reduce conflict, for example by adopting the "jothaan" attitude or avoiding communication with the disputing parties. They also apply the concept of "nglurug tanpa bala, menang tanpa ngasorake," which encourages a wise resolution of conflict without humiliating the opposing party. This approach aims to maintain the honor of the opponent and avoid the emergence of resentment that can be passed on to the next generation. Javanese families adhere to the concept of dwi tunggal, namely joint power between the father and mother, although the final decision is usually in the hands of the father, which makes this system considered paternalistic. The wife plays an important role, especially in managing the household economy, making her position equal to her husband. This research is a case study using a holistic qualitative approach. With this approach, the emphasis of the study is on providing an explanation of a social phenomenon using other social phenomena and cultural elements that exist and apply in the community concerned. The purpose of this study is to determine the ecological mapping of Javanese families in the Muslim plantation employee community in Asahan Regency. As well as the dynamics of the quality of family functioning in Javanese families in the Muslim plantation employee community in Asahan Regency. From this study it was found that the ecology of Javanese families in the plantation employee community in Asahan Regency experienced changes that were not linear in historical sequence because political geography factors played a role in determining the pattern of community production.